(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The experience report presented here highlights the impact of COVID-19 in carrying out the academic planning of PET Librarianship in 2020, in particular, the exhibition of films for debates as a space for reflection on sociopolitical agendas. The document’s general objective is to demonstrate the adaptations required during the activities, the holding of events in virtual space and the importance of research and scientific dissemination in a quarantine period, and as specific, to identify and characterize the guidelines extracted from the audiovisual as a composition of material for debate. The methodology used is based on the concepts acquired through the indicated bibliographies and on the observation of the adaptive approach in the event. It is concluded that the realization of CinePET in the adaptive context of pandemic and quarantine provided a new perspective on the valorization of scientific research in Brazil and the importance of media and technologies for the production and dissemination of information.